Parallel algorithm for solving coupled algebraic Lyapunov equations of discrete-time jump linear systems - Borno, I.; Gajic, Z. (Computers & mathematics with applications (1987), 1995)
A parallel iterative scheme for solving coupled algebraic Lyapunov equations of discrete-time jump linear systems with Markovian transitions is introduced. The algorithm is computationally efficient since it operates on reduced-order decoupled algebraic discrete Lyapunov equations. Furthermore, the solutions at every iteration are computed by elementary matrix operations. Hence, the number of operations is minimal. Monotonicity of convergence is established under the existence conditions of unique positive solutions.